Problem-Based Learning E-Book for Natural and Social Sciences in Fourth-Grade of Elementary Schools - Ardika, Gede; Sukmana, Adrianus I Wayan Ilia Yuda; Sudarma, I Komang (Jurnal Pedagogi dan Pembelajaran, 2024)
This study was motivated by the low achievement levels of students in the Natural and Social Sciences (IPAS) subject. This issue arises from the lack of instructional materials that adequately support the learning process. The research aims to develop a problem-based learning e-book for fourth-grade IPAS in elementary schools. This is a development study employing the ADDIE model, which consists of five systematic stages: analysis, design, development, implementation, and evaluation. The study involved three experts (content, design, and media) and nine students in a small-group trial. Data collection methods included interviews, observations, questionnaires, and tests. Data analysis employed qualitative and quantitative techniques, as well as inferential statistics. The results indicated that the e-book achieved "very good" qualifications in terms of validity and user response. Furthermore, the effectiveness test, based on t-test calculations, revealed significant differences in learning outcomes before and after using the problem-based learning e-book. The post-test scores exceeded the Minimum Competency Standards (KKTP), indicating that the problem-based learning e-book effectively improved the learning outcomes of fourth-grade students in the IPAS subject. The innovation of e-books based on problem-based learning in the content of the fourth grade science subjects in elementary schools has implications for increasing learning outcomes and student abilities in the content of science subjects with e-book teaching materials, and can hone teachers' abilities in the field of technology.